Single center experience with ABO-incompatible and ABO-compatible pediatric heart transplantation - Rosenthal, L. Lily; Spickermann, Tabea Katharina; Ulrich, Sarah Marie; Dalla Pozza, Robert; Netz, Heinrich; Haas, Nikolaus A.; Schramm, René; Schmoeckel, Michael; Hagl, Christian; Hörer, Jürgen; Michel, Sebastian; Grinninger, Carola (Frontiers in Transplantation, 2024)
IntroductionThe aim of this study was to analyze the results after pediatric heart transplantation (pHTx) at our single center differentiating between ABO-incompatible (ABOi) and -compatible (ABOc) procedures.Methods and patientsWe retrospectively analyzed outcomes of ABO-incompatible HTx procedures performed at our center and compared the data to ABO-compatible HTx of the same era. Eighteen children (<17 months) underwent pediatric HTx and seven of them underwent ABO-incompatible HTx between 2003 and 2015.ResultsMechanical circulatory support as bridge to transplant was necessary in 3/7 patients before ABO-incompatible HTx and in 3/11 patients before ABO-compatible HTx. Mean waiting time on the list was 36 ± 30 days for ABO-incompatible HTx and 86 ± 65 days for ABO-compatible HTx. The 5-years re-transplant free survival was 86% following ABO-incompatible and 91% after ABO-compatible. In the cohort undergoing ABO-incompatible HTx, 2 patients showed an acute cellular rejection, while early graft failure was not observed. In the cohort undergoing ABOcompatible HTx, acute cellular rejection was observed in 9/11 patients, with early graft failure occurring in nine and CVP in two. A total of ten children were listed for ABO-incompatible HTx after 2015; however, all ten underwent an ABO-compatible transplantation.DiscussionThis study adds much needed information to the literature on ABOi-HTx by showing with a retrospective single center analysis that it is safe and leads to shorter waiting times. We conclude that strategies for ABOi-HTx should be elaborated further, potentially allowing more timely transplantation and thereby preventing waiting list complications such as the need for mechanical circulatory support and even death.